2019
DOI: 10.1016/j.jmbbm.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal characterization of polymeric gels to determine the influence of testing method on observed elastic modulus

Abstract: Demand for materials that mechanically replicate native tissue has driven development and characterization of various new biomaterials. However, a consequence of materials and characterization technique diversity is a lack of consensus within the field, with no clear way to compare values measured via different modalities. This likely contributes to the difficulty in replicating findings across the research community; recent evidence suggests that different modalities do not yield the same mechanical measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…An immobilized form of CALB, known as Novozym 435 (N435), is commercially available and has been commonly used by our group and others. N435 is enantioselective and regioselective, enabling a one-pot synthesis of copolymerizations with multifunctional monomers (functionality ≥ 3). Furthermore, steric constraints in the active site of CALB decrease the tendency of two chains undergoing cross-linking reactions . This study builds on previous work where lipase catalysis was effective for preparing high-molecular-weight glycerol-containing polyesters .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…An immobilized form of CALB, known as Novozym 435 (N435), is commercially available and has been commonly used by our group and others. N435 is enantioselective and regioselective, enabling a one-pot synthesis of copolymerizations with multifunctional monomers (functionality ≥ 3). Furthermore, steric constraints in the active site of CALB decrease the tendency of two chains undergoing cross-linking reactions . This study builds on previous work where lipase catalysis was effective for preparing high-molecular-weight glycerol-containing polyesters .…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, steric constraints in the active site of CALB decrease the tendency of two chains undergoing cross-linking reactions. 26 This study builds on previous work where lipase catalysis was effective for preparing high-molecular-weight glycerol-containing polyesters. 27 Enzyme catalysts serve as a substitute for toxic heavy metal catalysts in polymer synthesis, while also preserving the structures of thermally or chemically sensitive monomers.…”
Section: ■ Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The critical strain ε c for the onset of the wrinkle formation is given by ε c = 0.25­(3 E̅ s / E̅ f ) 2/3 , where E̅ = E /(1 – ν 2 ) is the plane-strain modulus with E being the Young’s modulus, ν the Poisson’s ratio, and the subscripts f and s denote the film and substrate, respectively . Using E f = 150 GPa, ν f = 0.38, E s = 0.04 MPa, and ν s = 0.5, we obtain ε c = 0.00003. The compressive strain ε in the film on the substrate can be estimated by measuring the change in the surface area due to wrinkle formation.…”
Section: Resultsmentioning
confidence: 99%
“…However, gel materials are challenging to characterize using conventional testing methods due to the low internal forces that these materials can withstand. A recent study found that different testing modalities do not necessarily produce the same mechanical measurements within a material [ 28 ]. This characteristic is more evident for high to very-high loading (or strain) rates in which the mechanical behavior is a function of the strain rate.…”
Section: Introductionmentioning
confidence: 99%